(untitled) (VERITAS LEGIS JOURNAL, 2026)
Foreign legal literature has been creating an interdisciplinary methodological basis for the economic analysis of law for a relatively long time, which is dictated by the need to find the most optimal model of legal regulation, including when determining variables that affect the formation of legal policy. It is worth noting that the methodology of scientific analysis previously used by legal science did not include economic analysis, undeservedly excluding this important toolkit for private law. In our understanding, the definition of an interdisciplinary approach in the formation of certain civil law structures should certainly serve the idea of determining the most effective, rational and viable model of interaction between economics, law and social relations. As a separate issue, it is proposed to consider the issue of institutionalizing economic analysis in improving corporate law in the context of increasing the economic efficiency of law enforcement practice. Actually, there are a lot of problems associated with the implementation of an interdisciplinary approach of economic and legal analysis in corporate law, ranging from the problems of theorizing transaction costs, conflict of directors, shareholders and creditors to the hypothesis of market efficiency (Efficient Market Hypothesis), the economics of mergers and acquisitions. In this context, our work does not pretend to be a depth of study of these processes, however, it is intended to determine the most important aspects of the interaction of economics and law in the further improvement of corporate law in the Republic of Kazakhstan.